2011
DOI: 10.3892/etm.2011.403
|View full text |Cite
|
Sign up to set email alerts
|

Repair of meniscal defect using an induced myoblast-loaded polyglycolic acid mesh in a canine model

Abstract: Defects of the meniscus greatly alter knee function and predispose the joint to degenerative changes. The purpose of this study was to test a recently developed cell-scaffold combination for the repair of a critical-size defect in the canine medial meniscus. A bilateral, complete resection of the anterior horn of the medial meniscus was performed in 18 Beagle canines. A PLGA scaffold was implanted into the defect of one knee of 6 canines and the contralateral defect was left untreated. Scaffolds loaded with au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 23 publications
(25 reference statements)
0
23
0
4
Order By: Relevance
“…Cells migrated to the tears injury site while promoting bridging across the site [64] Myoblast High cell yield, rapid proliferation activity with similar biochemical compositions compared to control [66] Articular chondrocytes Cells proliferated and synthesized ECM production (collagen & gag) [68] High proliferation rates and the tissue generated had notable amount of GAG and collagen type II [66] Cells infiltrated rapidly and distributed evenly in vitro and in vivo at Day 14 [69] Chondrocytes able to synthesized meniscal tissue in an in vivo situation [69] Mature cells Fibrochondrocytes Cells survived and proliferated for over 28 days, demonstrating the feasibility of culturing cells within ECM scaffolds [70] The cells manages to self assemble and produced ECM matrix of collagen type I and proteoglycans [71] Fibroblasts Fibroblastic cell morphology attached and infiltrated into the surface of scaffolds [75] the meniscus regeneration through in vitro and in vivo. It was revealed that the tendon grafts with synovial MSCs succeeded to induce early phase of synovial coverage at the defect site and had better integration with the meniscus defect that promote meniscus regeneration compared to control group [61].…”
Section: Type Of Cells Results Referencesmentioning
confidence: 99%
“…Cells migrated to the tears injury site while promoting bridging across the site [64] Myoblast High cell yield, rapid proliferation activity with similar biochemical compositions compared to control [66] Articular chondrocytes Cells proliferated and synthesized ECM production (collagen & gag) [68] High proliferation rates and the tissue generated had notable amount of GAG and collagen type II [66] Cells infiltrated rapidly and distributed evenly in vitro and in vivo at Day 14 [69] Chondrocytes able to synthesized meniscal tissue in an in vivo situation [69] Mature cells Fibrochondrocytes Cells survived and proliferated for over 28 days, demonstrating the feasibility of culturing cells within ECM scaffolds [70] The cells manages to self assemble and produced ECM matrix of collagen type I and proteoglycans [71] Fibroblasts Fibroblastic cell morphology attached and infiltrated into the surface of scaffolds [75] the meniscus regeneration through in vitro and in vivo. It was revealed that the tendon grafts with synovial MSCs succeeded to induce early phase of synovial coverage at the defect site and had better integration with the meniscus defect that promote meniscus regeneration compared to control group [61].…”
Section: Type Of Cells Results Referencesmentioning
confidence: 99%
“…Myoblast loaded PLGA scaffolds have been evaluated for the repair of inner meniscal defects [172]. A derivatised HA, HYADD4 ® hydrogel cell delivery system has been used for the repair of radial-longitudinal tears in a randomised controlled study [173].…”
Section: Bioscaffolds Bioactive Substances and Bioadhesives And Menimentioning
confidence: 99%
“…Os danos meniscais fazem parte das lesões mais comuns no joelho (24), frequentemente ocorrem devido a impactos durante a prática esportiva ou resultam da degeneração da articulação conforme o envelhecimento (1,14,15,20,25,26). A maioria das fraturas localizam-se nas partes avasculares do menisco (região sem espontânea regeneração) ocasionando dores acentuadas e mudanças degenerativas no conjunto do joelho, como a osteoartrose (2,5,(13)(14)(15)(16)18,20,25,27).…”
Section: Capítulo 10unclassified
“…As estratégias para correção das lesões são complexas. O procedimento ortopédicos mais empregado é a meniscectomia que consiste na remoção tecidual da área lesionada (5,14,15,19,21,22,24,(26)(27)(28)(29). Entretanto a diminuição do tecido conduz à perda das funções meniscais e consequentemente ao desenvolvimento da degeneração da cartilagem, perturbando a qualidade de vida dos pacientes (14,21,30).…”
Section: Capítulo 10unclassified